Per Cutaneous Plating Through Multiple Stab Incisions in Comminuted Fractures of The Tibia-A New Technique - FAISAL NAZEER HUSSAIN, MUHAMMAD USMAN UL, MUHAMMAD IQBAL (Journal of Fatima Jinnah Medical University, 2018)
Introduction: A study to assess the role of minimally invasive plate osteosynthesis (MIPO) in the treatment of 24 adult patients of comminuted fractures of the tibia is presented. Materials & Method: It was a prospective and interventional study of clinical cases being operated with minimally invasive plate osteosynthesis. However a new technique with multiple stab incisions was used. Results: There were 4 cases of proximal tibial fractures, 17 cases of diaphyseometaphyseal fractures and 3 cases of distal tibial fractures. All were treated with "Biological Plating" techniques using indirect reduction methods, with limited operative exposure, without opening the fracture site. A new multiple stab technique was used to fix these fractures. All cases went on to union. 62.5% cases showed radiological union between 14 and 18 weeks and remaining 37.5% in 19 and 23 weeks. 82.3% cases went to full weight bearing in 23 weeks. 8 cases required bone grafting. Incidence of complications was very low, with only 6 cases of superficial infection, delayed union, non union, implant failures. Range of motion at knee and ankle joint was excellent. Conclusion: The functional outcome for long term result were rated using points, revealed excellent to good outcome in 83% cases with fair result in 17% patients.